PENGARUH GAYA MENGAJAR TERHADAP HASIL BELAJAR SOSIOLOGI KELAS XI IIS SMA KEMALA BHAYANGKARI - Satibi, Sarah Berlinggi; Bahari, Yohanes; Stella Prancisca, Stella (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to analyze (1) the teaching style of teachers in class XI sociology learning at Kemala Bhayangkari High School. (2) student learning outcomes in class XI sociology learning at Kemala Bhayangkari High School. (3) the influence of the teacher"™s teaching style on student learning outcomes in class XI sociology learning at Kemala Bhayangkari High School. The method used in this research is quantitative with an ex-post facto type of correlational research. This research used a population of 60 respondents, namely class XI IIS students at Kemala Bhayangkari High School. The technique used in data collection was a Likert scale questionnaire which was distributed directly to respondents. Data analysis in this study used simple linear regression analysis assisted by the IBM SPSS 20 application with research results showing that: (1) the teacher"™s teaching style in class . (2) student learning outcomes in class (3) the influence of the teacher"™s teaching style on student learning outcomes as indicated by a sig.alpha of 0.0000.005 and a coefficient of determination of 0.414 or 41%